NILAI KEARIFAN LOKAL DALAM TRADISI PUNJUNGAN PERNIKAHAN PADA MASYARAKAT JAWA DESA O MANGUNHARJO KABUPATEN MUSI RAWAS TAHUN 2019-2024 - Hasanah, Uswatun; Miyarni, Ira; Irwansyah, Yadri (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
In this study, we're discussing the Lordship tradition. The pilgrimage tradition is the custom of giving food to those who will perform a feast. This study uses qualitative research methods. Qualitative research can be understood as a method of study that uses descriptive data in written or oral language from observable people and actors. Qualitative research procedures are descriptive processes that produce descriptive data of people and their behaviour which can be observed; this approach focuses on the background and individuals as a whole. Sources used are primary and secondary sources where all data clearly related to visitation can be used as research material. In this study, the techniques of data collection in these studies used various techniques, namely interviews, observations and documentation. In this study it was found that each region has its own culture and customs, which allows for many cultural differences from one area to another in Indonesia. In this study found in the village of O. Mangunharjo. The tradition of visitation has become the custom held before a wedding ceremony. Although today it is a modern and versatile era, the tradition of visitation remains in use by people in Mangunharjo village.